Axial compressive behavior of concrete filled stainless-carbon steel tube columns: Experimental investigation. (October 2021) - Qiao, Qiyun; Li, Jiafeng; Yang, Zhaoyuan; Cao, Wanlin; Yang, Jing; Zhang, Wenwen
Abstract: This paper investigates the axial compressive behavior of concrete-filled stainless-carbon steel tube (CFSCT) stub columns, consisting of an outer stainless steel tube, an inner carbon steel tube, and infilled concrete. A total of twenty column specimens are fabricated and tested. Test parameters include column section type, strength and wall thickness of carbon steel tube, and concrete strength. Failure modes, load versus deformation relationships, ultimate strength, residual strength, ductility, elastic and elastic-plastic local buckling stress, and strain characteristics are investigated. Results show that outward local buckling of stainless steel tubes occurs in all CFSCT column specimens, and columns fail in a ductile manner. Increasing the carbon steel tube thickness can significantly improve column ultimate strength and residual strength. Compared to conventional concrete-filled stainless steel tube (CFSST) columns, the ultimate strength of CFSCT columns improved by 10.9%, 23.1%, and 27.4% on average for columns with carbon steel tube wall thickness of 2, 4, and 6 mm, respectively. The post-peak ductility behavior is also related to carbon steel tube wall thickness, increasing wall thickness can slow down the descending branch after peak load. Concrete has significant effect on the ultimate strength, when concrete strength increases, specimen ultimate strength increases by 15.1% on average. In addition, finite element model is established and analyzed based on the experimental results. Finally, ultimate strengths are compared and evaluated according to the Eurocode 4, AIJ, ACI and GB 50936. Highlights: An innovative concrete filled stainless-carbon steel tube column is studied. Twenty column specimens including circular and square sections are fabricated and tested. Failure mode, load versus deformation relationships, strength, ductility, and strain characteristics are investigated. Ultimate strengths are compared and evaluated according to the Eurocode 4, AIJ, ACI, and GB 50936.